2015
DOI: 10.1159/000441957
|View full text |Cite
|
Sign up to set email alerts
|

Left Renal Cortical Thickness Measured by Ultrasound Can Predict Early Progression of Chronic Kidney Disease

Abstract: Aims: The kidney becomes atrophic in advanced chronic kidney disease, and renal size and parenchymal volume correlate with renal function. However, alterations in renal parenchymal volume have not been adequately studied in terms of the renal cortex and medulla. We investigated the relationship between the changes in the renal cortex and medulla and renal function. Methods: Renal ultrasound (US) parameters including renal length, parenchymal thickness, cortical thickness and medullary thickness were assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Morphological parameters including length, cortical thickness and medullary thickness could be measured from all the patients, except that volumetric calculations were impossible in six patients. In order to eliminate influence from sex and body size, kidney morphological parameters were adjusted by height and body surface area as previously reported [15]. Referencing kidney morphological parameters to height diminished the sex differences, thus height-adjusted values were used thereafter in this study (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological parameters including length, cortical thickness and medullary thickness could be measured from all the patients, except that volumetric calculations were impossible in six patients. In order to eliminate influence from sex and body size, kidney morphological parameters were adjusted by height and body surface area as previously reported [15]. Referencing kidney morphological parameters to height diminished the sex differences, thus height-adjusted values were used thereafter in this study (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Despite that kidney structure is associated with renal function, little attention has been paid to the potential utility of morphological assessment for detecting earlier stages of CKD until recently. Small number of cross-sectional studies with enhanced computed tomography [7] or ultrasonography [15] suggested thinning of cortical thickness precedes that of medulla or length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several imaging studies have shown that a lower cortical thickness is associated with reduced renal function as measured by eGFR [88][89][90][91]. In the case of advanced disease, the reduction in cortical thickness can be severe enough such that it approaches the typical dimensions of the ASL voxels, significantly reducing the number of pure cortex voxels from which cortical RBF can be estimated.…”
Section: Quantificationmentioning
confidence: 99%
“…Moreover, a meta‐analysis suggests that, in five different unilateral anomalies: multicystic dysplastic kidney, renal agenesis/aplasia, renal ectopia, pelviureteral junction obstruction, and nonobstructive nonrefluxing megaureter, the left side was affected in 53%, 57%, 56.9%, 63.2%, and 62.5% of patients, respectively, which were significantly different from the anticipated 50% anomalies . Moreover, left cortical thickness, but not right cortical thickness could help to detect early changes in renal functions . The right kidney–liver echogenicity ratio but not the left kidney–spleen echogenicity ratio showed a close relationship with decreased renal function when increased .…”
mentioning
confidence: 96%